Changing Space, Changing City Johannesburg after apartheid - Wray, Chris; Todes, A.; Götz, Graeme; Harrison, Philip, 1964-; Project Muse. (Wits University Press, 2014)
"As the dynamo of South Africa\2019s economy, Johannesburg commands a central position in the nation\2019s imagination, and scholars throughout the world monitor the city as an exemplar of urbanity in the global South. This richly illustrated study offers detailed empirical analyses of changes in the city\2019s physical space, as well as a host of chapters on the character of specific neighbourhoods and the social identities being forged within them. Informing all of these is a consideration of underlying economic, social and political processes shaping the wider Gauteng region. A mix of respected academics, practising urban planners and experienced policymakers offer compelling overviews of the rapid and complex spatial developments that have taken place in Johannesburg since the end of apartheid, along with tantalising glimpses into life on the streets and behind the high walls of this diverse city. The book has three sections. Section A provides an overview of macro spatial trends and the policies that have infl uenced them. Section B explores the shaping of the city at district and suburban level, revealing the peculiarity of processes in different areas. This analysis elucidates thelarger trends, while identifying shifts that are not easily detected at the macro level. Section C is an assembly of chapters and short vignettes that focus on the interweaving of place and identity at a micro level. With empirical data supported by new data sets including the 2011 Census, the city\2019s Development Planning and Urban Management Department\2019s information system, and Gauteng City-Region Observatory\2019s substantial archive, the book is an essential reference for planning practitioners, urban geographers, sociologists, and social anthropologists, among others."--Publisher description.
1. Materialities, subjectivities and spatial transformation in Johannesburg -- Section A. The macro trends. 2. The \2018thin oil of urbanisation\2019? : Spatial change in Johannesburg and the Gauteng city-region -- 3. Poverty and inequality in the Gauteng city-region -- 4. The impact of policy and strategic spatial planning -- 5. Tracking changes in the urban built environment : An emerging perspective from the City of Johannesburg -- 6. Johannesburg\2019s urban space economy -- 7. Changes in the natural landscape -- 8. Informal settlements -- 9. Public housing in Johannesburg -- 10. Transport in the shaping of space -- 11. Gated communities and spatial transformation in Greater Johannesburg -- Section B. Area-based transformations. 12. Between fixity and flux: Grappling with transience and permanence in the inner city -- 13. Are Johannesburg\2019s peri-central neighbourhoods irremediably \2018fluid\2019? : Local leadership and community building in Yeoville and Bertrams -- 14. The wrong side of the mining belt? Spatial transformations and identities in Johannesburg\2019s southern suburbs -- 15. Soweto.: A study in socio-spatial differentiation -- 16. Kliptown: Resilience and despair in the face of a hundred years of planning -- 17. Alexandra -- 18. Sandton Central, 1969\20132013. From open veld to new CBD? -- 19. In the forest of transformation.: Johannesburg\2019s northern suburbs -- 20. The north-western edge -- 21. The 2010 World Cup and its legacy in the Ellis Park Precinct : Perceptions of local residents -- 22. Transformation through transportation: Some early impacts of Bus Rapid Transit in Orlando, Soweto -- Section C: Spatial identities. 23. Footprints of Islam in Johannesburg -- 24. Being an immigrant and facing uncertainty in Johannesburg : The case of Somalis -- 25. On \2018spaces of hope\2019: Exploring Hillbrow\2019s discursive credoscapes -- 26. The Central Methodist Church -- 27. The Ethiopian Quarter -- 28. Urban collage : Yeoville -- 29. Phantoms of the past, spectres of the present : Chinese space in Johannesburg -- 30. The notice -- 31. Inner-city street traders : Legality and spatial practice -- 32. Waste pickers/informal recyclers -- 33. The fear of others : Responses to crime and urban transformation in Johannesburg -- 34. Black urban, black research : Why understanding space and identity in South Africa still Matters.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Johannesburg (South Africa); Sociology, Urban -- South Africa -- Johannesburg; Urban policy -- South Africa -- Johannesburg; City planning -- South Africa -- Johannesburg; Electronic books